The Output Decline in the Aftermath of Reform : The Cases of Bulgaria, Czechoslovakia, and Romania - Ostry, Jonathan; Borensztein, Eduardo; Demekas, Dimitri (Washington, D.C. : International Monetary Fund, 1992)
This paper analyzes the declines in economic activity experienced by Bulgaria, the Czech and Slovak Federal Republic (CSFR), and Romania in the period since the initiation of market-oriented reforms in these countries. The paper reviews developments in the three countries and empirically investigates two questions that are key to the interpretation of the output decline: First, to what extent does the output fall reflect 'structural change' (or a reallocation of resources across sectors) rather than a conventional recession? Second, to what extent have demand-side or supply-side forces been dominant in generating the output decline?.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet